PENERAPAN METODE PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS VIIB SMP WIDYA SAKTI DENPASAR TAHUN PELAJARAN 2023/2024 - Yuniari, Ni Ketut; Indrawati, IGA Putu Tuti; Wedasuwari, Ida Ayu Made (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research is classroom action research (CAR) which aims to 1) Find out how to improve reading comprehension skills through the SQ3R learning method in class VII B students at Widya Sakti Middle School, Denpasar; 2) Knowing the steps of the SQ3R learning method in improving reading comprehension skills in class VII B students at Widya Sakti Middle School, Denpasar. Data collection was carried out by observation and tests. The data that has been obtained is analyzed using qualitative and quantitative analysis methods. The research results obtained showed that there was an increase in reading comprehension skills through the SQ3R method. This increase can be seen from the initial test score, namely 40.15, which then increased in cycle I to 49.62, increasing again in cycle II to 61.82. Compared to cycle II, the average student score increased better to 80 in cycle III. The steps of the SQ3R method are 1) Survey: students are asked to observe the fantasy story text by reading parts of the text, 2) Qquestion: students are asked to understand the questions given by the teacher, 3) Read: students are given a certain amount of time it takes longer to read the entire content of the reading and find answers to the questions that have been given, 4) Recite: after reading the whole story, students are asked to answer the questions that have been given without opening the answer book, 5) Review: students are asked to review briefly all questions and answers.